2021
DOI: 10.3390/genes12010105
|View full text |Cite
|
Sign up to set email alerts
|

An 8.22 Mb Assembly and Annotation of the Alpaca (Vicugna pacos) Y Chromosome

Abstract: The unique evolutionary dynamics and complex structure make the Y chromosome the most diverse and least understood region in the mammalian genome, despite its undisputable role in sex determination, development, and male fertility. Here we present the first contig-level annotated draft assembly for the alpaca (Vicugna pacos) Y chromosome based on hybrid assembly of short- and long-read sequence data of flow-sorted Y. The latter was also used for cDNA selection providing Y-enriched testis transcriptome for anno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(215 reference statements)
1
2
0
Order By: Relevance
“…This region is in the distal part of the Y-chromosome for all the species studied, but in BTA/OAR/CHI/SSC it is at the telomere of the p-arm, while in ECA/BBU it was reported at the telomere of the q-arm ( Figure 2 ). In addition, very recently, the same position has been confirmed also in VPA [ 75 ]. In particular, in this species, the Y-chromosome is very small and does not show distinct cytogenetic characteristic, so that it is difficult to identify the location of the centromere.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This region is in the distal part of the Y-chromosome for all the species studied, but in BTA/OAR/CHI/SSC it is at the telomere of the p-arm, while in ECA/BBU it was reported at the telomere of the q-arm ( Figure 2 ). In addition, very recently, the same position has been confirmed also in VPA [ 75 ]. In particular, in this species, the Y-chromosome is very small and does not show distinct cytogenetic characteristic, so that it is difficult to identify the location of the centromere.…”
Section: Discussionsupporting
confidence: 55%
“…In particular, in this species, the Y-chromosome is very small and does not show distinct cytogenetic characteristic, so that it is difficult to identify the location of the centromere. Only with the use of the FISH technique by PAR BACs, it has been demonstrated that the alpaca Chr Y is submetacentric with a very small and short p-arm and the PAR located at the telomere in the long q-arm [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation